The first apicoplast tRNA thiouridylase plays a vital role in the growth of Toxoplasma gondii - Yang, Yimin; Lin, Mi; Chen, Xueqiu; Zhao, XianFeng; Chen, Lulu; Zhao, Mingxiu; Yao, Chaoqun; Sheng, Kaiyin; Yang, Yi; Ma, Guangxu; Du, Aifang (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasmosis caused by the protozoan Toxoplasma gondii is one of the most common parasitic diseases in humans and almost all warm-blooded animals. Lys, Glu, and Gln-specific tRNAs contain a super-modified 2-thiourea (s2U) derivatives at the position 34, and s2U34 modification is essential for all living organisms, by maintaining the structural stability and aminoacylation of tRNA, and the precision and efficiency of codon recognition during protein translation. However, the enzyme(s) involved in this modification in T. gondii remains elusive. In this report, three putative tRNA-specific 2-thiolation enzymes were identified, of which two involved in s2U34 modification of tRNALys, tRNAGlu, and tRNAGln. One was named TgMnmA, an apicoplast-located tRNA-specific 2-thiolation enzyme in T. gondii. Using TgMnmA knockout we found that TgMnmA is important for the lytic cycle of tachyzoites. Furthermore, loss of TgMnmA led to abnormity of the apicoplast biogenesis and severely disturbed apicoplast genomic transcription. Most importantly, TgMnmA knockout exhibited much reduced virulence in mice. These findings provide new insights into s2U34 tRNA modification in Apicomplexa, and highlights TgMnmA, the first apicoplast tRNA thiouridylase of all apicomplexans, as a potential drug target.